Fujairah, United Arab Emirates. Archaeological investigations at multiple tomb sites in Dibba. Season 2019 - Pfeiffer, Kristina; Forster, Christoph; Ladurner, Mechthild; Lora, Sebastiano; Petiti, Emmanuele; Reichmuth, Silvio (e-Forschungsberichte des DAI, 2020)
In cooperation with the Fujairah Tourism & Antiquities Authority, research and rescue activities were continued at two Bronze and Iron Age sites in Dibba. In the area of Dibba Murba there are more than five collective tombs with rich find assemblages. This site, which has heavily been threatened by looting and gravel mining, was further excavated and consolidated in preparation for further measures. In the context of the superordinate question of changes in the lifestyle and nutrition of the population during cultural and climatic upheavals in the 2nd millenium BCE, the archaeo-anthropological excavations of the Iron Age layers at the multiple tomb of Dibba 76 were also continued.